2018
DOI: 10.14814/phy2.13636
|View full text |Cite
|
Sign up to set email alerts
|

Muscle phenotype is related to motor unit behavior of the vastus lateralis during maximal isometric contractions

Abstract: Previous investigations have reported a relationship between skeletal muscle phenotype and motor unit (MU) firing parameters during submaximal contractions. The purpose of the current investigation, however, was to examine the relationships between motor unit firing behavior during a maximal voluntary contraction, Myosin Heavy Chain (MHC) isoform content, and various molecular neuromuscular targets of the vastus lateralis (VL) muscle in resistance‐trained men. Ten resistance‐trained males completed a trapezoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 38 publications
6
15
0
Order By: Relevance
“…18,36 Despite similar activity levels, males displayed greater contractile tissue (larger mCSA, lower mEI), which might help explain the greater age-related decline in muscle thickness for males than females. 22 In line with previous studies, 8,10,11,37 MUAP waveforms discriminated from the surface EMG signal demonstrated a systematic pattern for all subjects, with higher-threshold MUs exhibiting larger peak-to-peak amplitudes for the VL. Initially, these findings would seem to be in disagreement with Del Vecchio et al 38 who reported weak or no relationships between the root mean square (RMS) of MUAPs via a spike trigger averaging (STA) technique and RTs.…”
Section: Discussionsupporting
confidence: 88%
“…18,36 Despite similar activity levels, males displayed greater contractile tissue (larger mCSA, lower mEI), which might help explain the greater age-related decline in muscle thickness for males than females. 22 In line with previous studies, 8,10,11,37 MUAP waveforms discriminated from the surface EMG signal demonstrated a systematic pattern for all subjects, with higher-threshold MUs exhibiting larger peak-to-peak amplitudes for the VL. Initially, these findings would seem to be in disagreement with Del Vecchio et al 38 who reported weak or no relationships between the root mean square (RMS) of MUAPs via a spike trigger averaging (STA) technique and RTs.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, in the present study, we observed a more negative slope in the GlyGly than the ArgArg group during muscle actions performed at 50% MVIC, but a less negative slope in the GlyGly and ArgGly groups than in the ArgArg group during muscle actions performed at 70% MVIC (Figure ). Thus, our results, in combination with these previous studies (Colquhoun et al., ; Trevino et al., ), might suggest skeletal muscle fibre‐type differences for the β 2 ‐AR genotypes.…”
Section: Discussionsupporting
confidence: 85%
“…We observed not only that muscle strength was significantly greater in the GlyGly than the ArgArg group (Figure a), but also that MU behaviour was dependent on β 2 ‐AR genotype. Previous studies (Colquhoun et al., ; Trevino et al., ) have observed relationships between type I and type II fibre area and the slope of the MFR versus RT relationship. These studies appear to demonstrate that individuals with greater type II fibre content demonstrate a MFR versus RT relationship characterized by a more negative slope during low‐ to moderate‐force contractions, but a less negative slope during high‐force contractions.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…1. The MU properties calculated in the present investigation were RT, defined as the relative torque (%MVIC) at which the motor unit first discharged, and MFR, calculated as the average firing rate (pulses/s, pps) during the plateau in each individual MU's firing curve (Colquhoun et al 2018;Muddle et al 2018). Finally, the synaptic inputs received by the motoneuron pool were compared between torque levels.…”
Section: Methodsmentioning
confidence: 99%